SIRT3 controls brown fat thermogenesis by deacetylation regulation of pathways upstream of UCP1 - Rajaa Sebaa; Jeff Johnson; Chantal Pileggi; Michaela Norgren; Jian Xuan; Yuka Sai; Qiang Tong; Izabella Krystkowiak; Emma Bondy-Chorney; Norman E. Davey; Nevan Krogan; Michael Downey; et al. (Elsevier, 2019)
Objective: Brown adipose tissue (BAT) is important for thermoregulation in many mammals. Uncoupling protein 1 (UCP1) is the critical regulator of thermogenesis in BAT. Here we aimed to investigate the deacetylation control of BAT and to investigate a possible functional connection between UCP1 and sirtuin 3 (SIRT3), the master mitochondrial lysine deacetylase. Methods: We carried out physiological, molecular, and proteomic analyses of BAT from wild-type and Sirt3KO mice when BAT is activated. Mice were either cold exposed for 2 days or were injected with the β3-adrenergic agonist, CL316,243 (1 mg/kg; i.p.). Mutagenesis studies were conducted in a cellular model to assess the impact of acetylation lysine sites on UCP1 function. Cardiac punctures were collected for proteomic analysis of blood acylcarnitines. Isolated mitochondria were used for functional analysis of OXPHOS proteins. Results: Our findings showed that SIRT3 absence in mice resulted in impaired BAT lipid use, whole body thermoregulation, and respiration in BAT mitochondria, without affecting UCP1 expression. Acetylome profiling of BAT mitochondria revealed that SIRT3 regulates acetylation status of many BAT mitochondrial proteins including UCP1 and crucial upstream proteins. Mutagenesis work in cells suggested that UCP1 activity was independent of direct SIRT3-regulated lysine acetylation. However, SIRT3 impacted BAT mitochondrial proteins activities of acylcarnitine metabolism and specific electron transport chain complexes, CI and CII. Conclusions: Our data highlight that SIRT3 likely controls BAT thermogenesis indirectly by targeting pathways upstream of UCP1. Keywords: Brown adipose tissue, Thermogenesis, Thermoregulation, Mitochondria, Uncoupling protein 1, Sirtuin 3, Acetylation, Oxidative phosphorylation, Fatty acid oxidation, Acylcarnitines